Euphorbia helioscopia: Past, Present and Future Prospects - Maneesha Singh; Anju Rani; Dhananjay Kumar Gupta (Advances and Challenges in Science and Technology Vol. 5, 2023)
The Euphorbia is the largest genus in the plant family Euphorbiaceae, comprising about 300 genera and 2,000 known species. All species of Euphorbia are characterized by cyathium inflorescence and the production of a white latex that is rich in secondary metabolites especially terpenoids responsible for diverse biological activities. Sun spurge (Euphorbia helioscopia L., Euphorbiacae family) is an annual plant, native to most of northern Africa, Europe, and eastward through most of Asia. It emerges from November to December and invades winter crops and vegetables, such as wheat, lentils, chickpeas, potatoes, and peas. The flowers are hermaphrodite (have both male and female organs) and are pollinated by flies. Seedlings of E. helioscopia exhibit epigeal germination. A literature review about this plant showed various types of biological activities such as antitumor, antiviral, antibacterial, nematicidal, antifungal, molluscicidal effects, etc. The presence of secondary metabolites revealed that the studied plant Euphorbia helioscopia can be used in the future for finding various biological potential.